Nutritional intake and body composition changes in a UCI World Tour cycling team during the Tour of Spain - Muros, J. J.; Sánchez-Muñoz, C.; Hoyos, J.; Zabala, M. (European Journal of Sport Science, 2019)
The aim of this study was to quantify the food intake of an International Cyclist Union (UCI) World Tour professional cyclist team and to analyse changes in body composition during the Tour of Spain. Nine male professional road cyclists (31.3 ± 3.0 years) volunteered to participate in the study. Nutritional data were collected each day throughout the 3-week Tour by two trained investigators who weighed the food ingested by the cyclists. Mean nutritional intake of the cyclists was as follows: carbohydrate, 12.5 ± 1.8 g/kg/day of body weight (BW) (65.0 ± 5.9%); fat, 1.5 ± 0.5 g/kg/day BW (17.9 ± 5.6%); and protein, 3.3 ± 0.3 g/kg/day BW (17.1 ± 1.6%). Intake of all micronutrients, except for folate, vitamin D and potassium (which were 78.7%, 46% and 84% of Recommended Dietary Allowances (RDA), respectively), exceeded the RDA. Height, weight, skinfolds, circumferences and diameters were taken following the guidelines outlined by the International Society for the Advancement of Kinanthropometry. Body density, body fat percentage, muscle mass, total muscle mass and fat mass of the arms and thighs were calculated. Percentage body fat, fat mass and upper arm fat mass significantly decreased (p < .05) after the Tour independent of the equation method used in the calculations. Total muscle mass remained unchanged. Generally, this sample of cyclists consumed more protein and less fat than the recommended amount and had low weight, BMI and fat mass. It is suggested that sports nutritionists design personalised diets in order to maintain a correct proportion of nutrients as well as controlling possible anthropometrical changes that could affect performance.